A prospective cohort study on the impact of healthy lifestyles on all-cause and cardiovascular disease mortality among adult residents in Guizhou province - Jie ZHOU; Ling LI; Ji ZHANG; Lisha YU; Yujin REN; Wei JI; Yingjiao MU; Tao LIU (Zhongguo gonggong weisheng)
ObjectiveTo investigate the impact of healthy lifestyles on all-cause and cardiovascular disease (CVD) mortality among adult residents in Guizhou province, and to provide a reference for reducing mortality risk in the local population. MethodsA prospective cohort study was conducted using a multi-stage cluster random sampling method to recruit 9 280 permanent residents aged ≥ 18 years in Guizhou province from November 2010 to December 2012 for a baseline survey. Two follow-up surveys were conducted in December 2016 to June 2020 and December 2023, respectively. After excluding participants with incomplete baseline lifestyle information and loss to follow-up, 9 085 adult residents were finally included. A multivariable Cox proportional hazards regression model was used to analyze the impact of healthy lifestyles on all-cause and CVD mortality among adult residents in Guizhou province. ResultsThe 9 085 adult residents in Guizhou province were followed up for 0.10 – 13.07 years, with an average follow-up of (11.73 ± 1.49) years. During the follow-up period, there were 594 all-cause deaths and 241 CVD deaths, with mortality rates of 6.5% and 2.7%, and mortality densities of 5.57/1 000 person-years and 2.26/1 000 person-years, respectively. Among the 9 085 adult residents in Guizhou province, 545 (6.0%), 1 841 (20.3%), 3 064 (33.7%), 2 419 (26.6%), and 1 216 (13.4%) had ≤ 3, 4, 5, 6, and ≥ 7 healthy lifestyle factors, respectively. The all-cause mortality densities during follow-up were 10.38/1 000 person-years, 6.74/1 000 person-years, 5.38/1 000 person-years, 4.82/1 000 person-years, and 3.69/1 000 person-years, respectively, and the CVD mortality densities were 4.31/1 000 person-years, 2.79/1 000 person-years, 2.25/1 000 person-years, 2.00/1 000 person-years, and 1.11/1 000 person-years, respectively. After adjusting for confounding factors such as sex, age, ethnicity, education level, marital status, residence, systolic blood pressure, diastolic blood pressure, fasting blood glucose (FBG), 2-hour postprandial blood glucose (PBG), total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C), the multivariable Cox proportional hazards regression analysis showed that the risks of all-cause mortality among adult residents in Guizhou province with 4, 5, 6, and ≥ 7 healthy lifestyle factors were 0.732 times (HR = 0.732, 95%CI: 0.542 – 0.990), 0.667 times (HR = 0.667, 95%CI: 0.499 – 0.893), 0.664 times (HR = 0.664, 95%CI: 0.490 – 0.900), and 0.566 times (HR = 0.566, 95%CI: 0.391 – 0.820) that of those with ≤ 3 healthy lifestyle factors, respectively. The risk of CVD mortality among adult residents in Guizhou province with ≥ 7 healthy lifestyle factors was 0.444 times (HR = 0.444, 95%CI: 0.236 – 0.833) that of those with ≤ 3 healthy lifestyle factors. ConclusionsThe more healthy lifestyle factors adopted by adult residents in Guizhou province, the lower their risks of all-cause and CVD mortality.